Anomalous diurnal variation of atmospheric potential gradient and air-Earth current density observed at Maitri, Antarctica - Jeeva, K.; Gurubaran, S.; Williams, E.R.; Kamara, A.K.; Sinha, Ashwini K.; Guha, A.; Selvaraj, C.; Nair, K.U.; Dhar, Ajay (2016)
The scope of this paper is to explore the mechanisms operating over Maitri (70.76°S, 11.74°E, 117m above mean sea level), a coastal Antarctic station, that produce an anomalous fair-weather diurnal pattern of the atmospheric electric potential gradient (PG) and air-Earth current density (AEC). The anomaly in the diurnal variations of AEC and the PG is displaying an ostensible minimum at ~10 UT and a diminished response to the thunderstorm over the African continent in the 14–16 UT time frame. The data sets (2005–2014, except 2012) of the PG, and to some extent, AEC, from Maitri, are used to explore this anomaly. It follows that the fair-weather electrical phenomena over Maitri can be ascribed to global electrified convection on the one hand and to regional phenomena like convection due to the replacement of warm air by katabatic winds on the other hand. The katabatic winds originate on the polar plateau and blow from ~130° at Maitri which are likely to transport various elements from the mountain slopes, and space charge from the polar plateau is expected to produce various disturbances in the PG and AEC monitored over the coastal Antarctica. This mechanism may be responsible for peaks in the early UT hours and also for the anomalous behavior of atmospheric electrical parameters observed at Maitri. Maitri data are compared with that of Carnegie cruise and Vostok to explain the source of anomaly.